Guía de estrategias lúdicas para potenciar el desarrollo de valores de niñas y niños de cuatro a cinco años del nivel de educación inicial 2, del taller infantil Nikobari. - Villena Valenzuela, Blanca Lissette (2014)
This research aims to an education in values lead the lives of students, which should be linked to the development of the skills of entry level 2, thus has established strategies and practical recreational games take them to their implementation in the classroom, these strategies remain a viable option for improving the quality of education at this level mechanism must be properly applied by teachers taking into account the requirements that the student group sue to contribute to the integral development of children and encourage them to feel able to make moral judgments and build through games and act upon them, directing the child to be a social being able to live, learn and teach . The proposal consist of the playful strategies guides for the values and educations for childs from 4 and 5 years old to Nikobari Taller Infantil in the Distrito Metropolitano of Quito,